Cognitive Diagnostic Analyses of the Progress in International Reading Literacy Study (PIRLS) 2011 Results - Duong Thi, Dan; Loye, Nathalie (Mesure et évaluation en éducation, 2019)
Despite the grand demand to receive diagnostic information about students’ difficulties in reading, there are very few tests specifically designed for diagnostic purposes. Therefore, many researches in cognitive diagnostic approach (CDA) use large-scale test results to provide fine and reliable diagnostic feedback on the strengths and weaknesses of students other than the total scores or percentiles ranks, which allow appropriate intervention. This study shows an example of the application of diagnostic modeling using data from 4,762 Canadian students who completed booklet 13 of the PIRLS test in 2011. The results highlight the potential for detailed diagnostic feedback of students’ strengths and weaknesses on the underlying skills identified in the test.